CORRELATION BETWEEN MALOCCLUSION SEVERITY LEVEL AND CARIES STATUS OF 12-14 YEARS OLD STUDENTS IN SMPN 5 MARABAHAN - Yuni Kusumawati; Diana Wibowo; Aulia Azizah (Universitas Lambung Mangkurat, 2023)
ABSTRACTBackground: South Kalimantan is one of the provinces in Indonesia that occupies the highest second of dental and oral health problems. One of the dental and oral health problems that often faced in school age group is malocclusion that is 15,6%. Malocclusion is an occlusion condition that is not right or an occlusion that deviates from normal condition. The said condition can be happened because tooth shape abnormalities and jaw size. The crowded tooth position can cause caries occurrence, because the overlapped tooth position can complicate in the process of tooth brushing. The food remains that accumulated formed plaque retention and if it’s left alone continually, it will form a cavity in the tooth, causing email demineralization called caries. Purpose: To find out the correlation between malocclusion severity levels and caries status of 12-14 years old students in SMPN 5 Marabahan Material and Methods: This research was an analytic observational with cross sectional approach. The respondents were 12-14 years old students in SMPN 5 Marabahan that were taken with simple random sampling method. The respondents were 47 people. Results: The malocclusion severity level on mild category was 24 people (51%) and the caries status on moderate category was 19 people (40%). The result of Spearman test is p=0,000 < 0,05. Conclusion: There is a correlation between malocclusion severity level and caries status of 12-14 years old students in SMPN 5 Marabahan.Keywords : Caries status, DMF-T Index, Index (MAL I),Malocclusion severity